2004
DOI: 10.1042/bst0320567
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional steps involved in the assembly of photosystem I in Chlamydomonas

Abstract: Assembly of the PSI (photosystem I) complex in eukaryotic photosynthetic organisms depends on the concerted interactions of the nuclear and chloroplast genetic systems. We have identified several nucleus-encoded factors of Chlamydomonas reinhardtii that are specifically required for the synthesis of the two large chloroplast-encoded reaction-centre polypeptides, PsaA and PsaB, of photosystem I and that function at plastid post-transcriptional steps. Raa1, Raa2 and Raa3 are required for the splicing of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The biosynthesis of the plant PSI complex depends on the coordinated expression of nuclear and plastid genes, the targeting of the subunits to their proper location within the chloroplast, the incorporation of the pigments and redox cofactors, and the correct assembly of the subunits to form a functionally active complex (18,19). Additional gene products have been identified by mutational analyses that may act as regulatory or scaffold proteins in the assembly of PSI.…”
Section: Photosystem I (Psi)mentioning
confidence: 99%
See 2 more Smart Citations
“…The biosynthesis of the plant PSI complex depends on the coordinated expression of nuclear and plastid genes, the targeting of the subunits to their proper location within the chloroplast, the incorporation of the pigments and redox cofactors, and the correct assembly of the subunits to form a functionally active complex (18,19). Additional gene products have been identified by mutational analyses that may act as regulatory or scaffold proteins in the assembly of PSI.…”
Section: Photosystem I (Psi)mentioning
confidence: 99%
“…The conserved chloroplast open reading frames Ycf3, Ycf4, and Ycf37 along with specific cyanobacterial proteins like BtpA and RubA appear to be involved in posttranslational steps of PSI assembly. Ycf3 was shown to interact with PsaA and PsaD (20), whereas Ycf4 is associated with a high molecular mass complex containing several PSI subunits (19). Ycf3 as well as ycf4 mutants from Chlamydomonas lack PSI complexes (21).…”
Section: Photosystem I (Psi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed over the past several years have indicated that these factors are important for RNA stability, splicing, and initiation of translation (68,69). TAB2, for example, is required for the synthesis of the chloroplast-encoded photosystem I reaction center polypeptides, PsaB.…”
Section: Html)mentioning
confidence: 99%
“…They form a molecular framework which is involved in regulatory events on most hierarchical levels during plastid-gene expression including transcription, RNA metabolism/maturation and translation (for an overview see Allison 2000; Barkan and GoldschmidtClermont 2000;Manuell et al 2004;Herrin and Nickelsen 2004;Rochaix et al 2004;Nickelsen 2003 and references herein). While the cloning of regulatory factors is progressing, the different rate-limiting steps during the expression of various chloroplast genes are still poorly defined.…”
Section: Introductionmentioning
confidence: 99%